Gene expression analysis of CDH1 and MUC5AC in selected BPIFB1 transfected and untransfected gastric cancer cell lines / Nor Azlin Safina Abdul Aziz - Abdul Aziz, Nor Azlin Safina (2020)
The human Bactericidal/Permeability-Increasing Fold containing family B, member 1 (BPIFB1), or also known as LPLUNC1, C20orf114, is a member of the BPI/LBP/PLUNC protein family. BPIFB1 differential expression patterns have been reported in several cancers such as nasopharyngeal carcinoma (NPC) and oral mucoepidermoid carcinoma (MEC), in gastric cancer (GC) the role of BPIFB1 is not known, but the expression of the gene has been reported in the stomach co-expressing E-cadherin (CDH1) together with making 5, tracheobronchial/gastric (MUC5AC), the two genes that had been implicated in GC. To investigate the role of BPIFB1 in GC development and its interactions with CDH1 and MUC5AC, overexpression of the gene was induced in in-vitro using three different GC cell lines; AGS, HGC-27 and MKN-45. Human BPIFB1 expression construct was first generated using Gateway cloning technology followed by transfection into the cell lines for generation of stable GC cell lines overexpressing BPIFB1. The localization of BPIFB1 was done through Lumio green and Hoechst staining in transfected GC cell lines. The present of BPIFB1 protein in a transfected GC cell line was detected through in gel Lumio Green Detection. To quantify the expression level of BPIFB1 in each of gastric carcinoma, expression of mRNA level of BPIFB1, CDH1 and MUC5AC were then performed via RT-PCR and quantitative Real-time PCR (qPCR) for the BPIFB1 transfected and non-transfected GC cells followed by statistical analysis. β -ACTIN, a housekeeping gene was always included in both RT-PCR and qPCR reaction. For BPIFB1 mRNA level, the expression increased in the transfected cells with the highest in AGS with the p=.003* followed by MKN-45 with the p=.009* and HGC-27 with the p=.015*. The expression of MUC5AC is upregulated in BPIFB1 transfected GC cells whereby the highest expression is observed in MKN-45 with the p=.05* followed by AGS with the p=.001* and HGC-27 with the p=.026*. CDH1 expression is downregulated in all BPIFB1 transfected GC cells with the lowest expression found in HGC-27 with the p=.001* followed by AGS with the p=.003* and MKN-45 with the p=.004*. Thus, induction of BPIFB1 overexpression in vitro in GC cells contributes to the decreased in CDH1 expression and increased in MUC5AC expression suggesting that BPIFB1 other than co-expressed in the gastric gland with the two genes also regulates gene expression. By inducing an over-expression of the BPIFB1 in the GC cell lines we have generated an in-vitro model to elucidate the role of BPIFB1 in GC and its interactions with CDH1 and MUC5AC the two genes implicated in GC. We found that the overexpression of BPIFB1 downregulated the expression of CDH1 and upregulated MUC5AC gene expression. This finding was supported by both RT-PCR and qPCR. Work at the protein level and in-vivo needs to be done to support and further validate these findings. Our findings suggest that BPIFB1 is differentially expressed in GC cell lines and regulate the expression of CDH1 and MUC5AC.